Photoreflectance study of partially relaxed epitaxial InGaAs on GaAs - Motyka, Marcin; Gelczuk, Łukasz; Dąbrowska-Szata, Maria; Serafińczuk, Jarosław; Kudrawiec, Robert; Misiewicz, Jan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Room temperature photoreflectance (PR) spectroscopy and high resolution X-ray diffraction (HRXRD) have been used to investigate InxGa1–xAs layers grown compressively by MOVPE on GaAs substrates, with different composition and thickness. HRXRD reveals that all the samples are partially relaxed and In composition has been determined for each of the samples. The effects of residual strain on the optical response of the samples, namely interband transitions and the valence band splitting, were analyzed by fitting the standard line shape form to the PR data. The energies determined experimentally as a function of indium content were compared to those obtained in the framework of the elastic strain theory for pseudomorphic layers. This comparison allows us to estimate the extent of strain relaxation and to determine the residual strain values in the samples. Furthermore, we revealed that the measured residual strain εres follows t–1/2 dependence on the epitaxial layers thickness t. This confirms the appropriateness of the nonequilibrium models (energy-balance models) for these structures.
Optica Applicata, Vol. 39, 2009, nr 3, s. 561-570
Keywords: optyka; III-V semiconductors; PR spectroscopy; X-ray diffraction; strain relaxation; gallium indium arsenide